2015
DOI: 10.1016/j.cyto.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the IL-23/IL-17 axis and the Th17/Treg balance in the pathogenesis and control of autoimmune arthritis

Abstract: The T helper (Th) cell subsets are characterized by the type of cytokines produced and the master transcription factor expressed. Th1 cells participate in cell-mediated immunity, whereas Th2 cells promote humoral immunity. Furthermore, the two subsets can control each other. Thereby, Th1-Th2 balance offered a key paradigm in understanding the induction and regulation of immune pathology in autoimmune and other diseases. However, over the past decade, Th17 cells producing interleukin-17 (IL-17) have emerged as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 143 publications
2
61
0
Order By: Relevance
“…2 The negative correlation of osteoblastogenesis and the IL-17A level in the synovial fluid in children with juvenile idiopathic arthritis (JIA) confirms the role of IL-17A in the lesion in bone structures. 15 The destruction of bone structures is also influenced by various proinflammatory mediators induced by IL-17A, such as IL-6, prostaglandin E2, nitric oxide, and others.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…2 The negative correlation of osteoblastogenesis and the IL-17A level in the synovial fluid in children with juvenile idiopathic arthritis (JIA) confirms the role of IL-17A in the lesion in bone structures. 15 The destruction of bone structures is also influenced by various proinflammatory mediators induced by IL-17A, such as IL-6, prostaglandin E2, nitric oxide, and others.…”
mentioning
confidence: 86%
“…1 IL-17A binds to its receptors -IL-17 receptor A/IL-17 receptor C-on synoviocytes, endothelial cells, fibroblasts and osteoblasts and stimulates production of pro-inflammatory cytokines, chemokines and other inflammatory mediators, and also, interacts synergistically with other proinflammatory cytokines such as IL-1, IL-6, and tumor necrosis factor alpha. 2,3 In the initial phases of chronic arthritis, IL-17A affects synovial hypercellularity. 4 A study conducted on the culture of synovial fibroblasts has shown that IL-17A stimulates the production of the vascular endothelial growth factor, which is important in the angiogenesis and the consequent synovial proliferation.…”
mentioning
confidence: 99%
“…The level of IL‐17 in the peripheral blood of RA patients was significantly higher than that of healthy people. IL‐17 could promote cell migration, activate osteoclasts and lead to inflammation and bone destruction …”
Section: T Cell Subsets Balance and Rheumatic Immune Diseasementioning
confidence: 99%
“…In contrast to tT reg cells, peripheral T reg cells express FOXP3 and CD25 only after activation and require the presence of TGF‐β . The regulatory mechanisms of T reg cells required to suppress effector cell proliferation are various, including cell–cell contact through the expression of the cytotoxic T lymphocytes–associated protein 4 (CTLA4), deprivation of IL‐2, expression of anti‐inflammatory cytokines (TGF‐β and IL‐10), or expression of granzyme A and activation of the perforin pathway …”
Section: Regulatory T Cellsmentioning
confidence: 99%